Characteristic Changes of Bioaerosols in Beijing and Tsogt-Ovoo During Dust Events - Dong, Xiaofei; Chen, Bin; Maki, Teruya; Shi, Guangyu; Duan, Minzheng; Khalid, Bushra (Frontiers in Environmental Science, 2022)
The dust events moving at high altitudes by westerly wind can transport aerosols from Asian deserts to eastern Asia deposition areas such as China. Aerosols do not include only mineral particles but also microbial particles, which are called as bioaerosols and impact the ecosystem and air environment of the deposition area. For identifying the airborne microbial communities transported from the source area to deposition area, bioaerosol samples were collected in the typical source region (Tsogt-Ovoo in Gobi deserts) and the deposition region (Beijing in Chinese industrial area) during the dust events and non-dust days were compared between both sampling sites. The microscopic observation using DAPI fluorescent techniques revealed that the concentration of bioaerosols increased during the dust events in the both source and deposition regions. For the community structures of airborne bacteria at both sites, the dust-event occurrences changed the structure of bacterial community, increased the diversity of bacterial communities during dust events. Some specific bacterial populations, such as the members of Bacteroidetes, are dominated during dust events. As the dust occurrence, there is the possibility that specific bacteria can maintain longer time in the atmosphere might be transported from source area to deposition area.